PRE-TRIAGE SYSTEM : A SOLUTION TO FACING SURGE OF PATIENT DURING OF COVID-19 PANDEMIC - Yuvita, Emilda; Fitriasari, Nikma; Harjayanti, Nofita Dwi (Jurnal Kedokteran Brawijaya)
It is difficult to predict the end of Covid-19 pandemic. The emergency department (ED) as the main access for health services in the hospital has the highest risk of infection and overwhelmed by surge of patients. Modification of the emergency service system by implementing a pre-triage system can be a solution to dealing with surge of patients. The results of the preliminary study succeeded in forming a pre-triage system model. The pre-triage system model was carried out by identifying patients with the risk of Covid-19 in ED and modification of the emergency service flow. The implementation of the pre-triage system requires the readiness of the emergency department’s team. The sample used was all staff of emergency department of X Hospital which total 30. The results showed that 23,3% of respondents had good category knowledge, 56,67 % respondents had sufficient category knowledge, and 20% had less knowledge. The level of readiness found that 90% of respondents are ready for implementation of the pre-triage system. The Chi-Square test result show that the level of knowledge of the pre-triage system is not related to readiness to implement the pre-triage system.